Integrating MRI-based geometry, composition and fiber architecture in a finite element model of the human intervertebral disc. (September 2018) - Stadelmann, Marc A.; Maquer, Ghislain; Voumard, Benjamin; Grant, Aaron; Hackney, David B.; Vermathen, Peter; Alkalay, Ron N.; Zysset, Philippe K.
Abstract: Intervertebral disc degeneration is a common disease that is often related to impaired mechanical function, herniations and chronic back pain. The degenerative process induces alterations of the disc's shape, composition and structure that can be visualized in vivo using magnetic resonance imaging (MRI). Numerical tools such as finite element analysis (FEA) have the potential to relate MRI-based information to the altered mechanical behavior of the disc. However, in terms of geometry, composition and fiber architecture, current FE models rely on observations made on healthy discs and might therefore not be well suited to study the degeneration process. To address the issue, we propose a new, more realistic FE methodology based on diffusion tensor imaging (DTI). For this study, a human disc joint was imaged in a high-field MR scanner with proton-density weighted (PD) and DTI sequences. The PD image was segmented and an anatomy-specific mesh was generated. Assuming accordance between local principal diffusion direction and local mean collagen fiber alignment, corresponding fiber angles were assigned to each element. Those element-wise fiber directions and PD intensities allowed the homogenized model to smoothly account for composition and fibrous structure of the disc. The disc's in vitro mechanical behavior was quantified under tension, compression, flexion, extension, lateral bending and rotation. The six resulting load-displacement curves could be replicated by the FE model, which supports our approach as a first proof of concept towards patient-specific disc modeling. Abstract : Graphical abstract: fx1 Abstract : Highlights: Distinct collagen fiber lamellae could be visualized using diffusion tensor imaging. A fully MRI-based finite element model of a human IVD was generated. In vitro biomechanical tests in six loading scenarios were conducted. The finite element model could reproduce the measured loading curves for the tested range.